Louisiana Black-bellied Whistling-Duck clutch characteristics in the presence of conspecific and interspecific brood parasitism - Dylan L. Bakner; Katie E. Miranda; Kevin M. Ringelman (Journal of Field Ornithology, 2022)
Black-bellied Whistling-Ducks (Dendrocygna autumnalis; Whistling-Duck) are undergoing a rapid range expansion northward and now breed throughout the Southeastern United States. As a facultative cavity-nesting species, they have the potential to compete with Wood Ducks (Aix sponsa) and Hooded Mergansers (Lophodytes cucullatus) for nest sites. Little is known about Whistling-Duck breeding biology, and estimates of clutch characteristics and rates of conspecific and interspecific brood parasitism (CBP and IBP, respectively) are lacking. We monitored Whistling-Duck nests in Louisiana to describe nesting chronology, clutch size of parasitized and unparasitized (normal) nests, and hatchability (i.e., the portion of eggs that hatched) for clutches of different sizes and types. We monitored a total of 558 nest boxes between 2020–2021 and determined the presence of brood parasitism for 231 Whistling-Duck nests. CBP was detected in 73 (31.6%) nests, and IBP was observed in 51 (22.1%) nests parasitized by Wood Ducks, two (0.9%) nests parasitized by Hooded Mergansers, and one nest contained eggs from all three species. Normal clutches were smaller (15.4 ± 4.4 eggs) than CBP clutches (26.1 ± 8.8 eggs) and mixed clutches (22.2 ± 5.3 eggs; clutches containing Wood Duck or Hooded Merganser eggs; all pairwise P < 0.0001). However, within clutch repeatability, estimates for egg morphology data (i.e., length, width, and mass) were low (< 0.40) for normal clutches, suggesting CBP went undetected. Of 180 fated nests used to determine hatchability, 66 (36.7%) were successful, 49 (27.2%) were abandoned, 64 (35.6%) were depredated, and one (0.6%) was nonviable. Considering successful nests, hatchability was high for all clutch size bins ranging from 67.4% (41–45 eggs) to 81.6% (11–15 eggs). Our study is the first to document Whistling-Ducks successfully hatching mixed-species broods, and such high productivity could be contributing to Whistling-Duck range expansion.